Implementation Of Puskeu Presisi Application Policy For The Verification Of Financial Accountability ByThe Indonesian Police Finance Center - Theresia Wamburye, Maria; Pramono, Sapto (Soetomo Magister Ilmu Administrasi, 2025)
This research aims to determine the quality of public services in processing population documents in the Klabala Subdistrict, Sorong City, Soutwest Papua Privice, along with supporting and inhibiting factors. This research is a type of qualitative research with a descriptive approach. The theory used in this research is the service quality theory according to Parasuraman, Zeithaml, and Berry in Mustofa, at.all (2020) with 5 (five) service dimensions, including tangible, reliability, responsiveness, assurance and empathy. Data collection for this research was carried out through observation, interviews, document study. Next, the data analysis used is data collection, data condensation, data presentation and drawing conclusions. The results of the research found that population document management services in Klabala Sub-district, Sorong City, in five dimensions of public services including tangible, reliability, responsiveness, assurance and empathy, show positive indications and support the realization of quality services in services, although they are still not optimal in the dimensions tangible (physical evidence). The supporting factors for public services are the existence of computers, printers, office stationery, the existence of social media What’Up and Face Book for communication with sub-district residents, the seriousness of service officers and sub-district officials in serving population and community documents. In general, administrators have brought the necessary required documents. Meanwhile, the inhibiting factors are the lack of computer equipment, lack of employees who can operate computers, and the absence of a WIFI internet network This research recommends that Klabala Village should try to: add computer equipment for population document services, carry out internal training in computer operational mastery for all Klabala Village employees and establish a WIFI internet network in coordination with the Sorong City Information and Communication Service.